Enhancing Project Management Governance in Digital Transformation: A Case Study on Deploying Simplified Togaf Artifacts - Budianto, Farhan Alif; Lubis, Muharman; Mukti, Iqbal Yulizar; Budianto, Setyo (Riviera Publishing, 2025)
Digital Transformation (DT) acceleration requires robust project management governance that tightly integrates Enterprise Architecture (EA) with agile project delivery. Although The Open Group Architecture Framework (TOGAF 10) is the leading EA standard, its complexity hinders adoption, especially for resource-limited organizations. This study tackles this challenge by proposing and validating a simplified TOGAF 10 framework called